Development of Assemblr Edu Learning Media based on Augmented Reality to Improve Elementary School Students’ Mathematics Problem Solving Ability - Fadilasari, Erina; Nugraheni, Nursiwi (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2025)
This study aims to develop educational media using Augmented Reality (AR) through the Assemblr Edu platform to enhance students' mathematical problem-solving skills related to flat geometric at Gugus Tengku Umar Elementary School, Central Java Province. The research method used Research and Development (R&D), following the Borg & Gall model, has been applied and streamlined into seven strategic stages. With a purposive sampling technique, the research subjects included experts, teachers, and students. Data were gathered through interviews, observations, surveys, and assessments. The techniques used for data analysis included the qualitative descriptive study of observation and interview results and the quantitative descriptive study to assess product feasibility scores. The findings indicated that the developed learning media demonstrated a high feasibility level, receiving an average score of 91% from material experts, 90% from media experts, and 82% from language experts. In addition, there was an increase in students' math problem-solving ability with an N-Gain of 0.72, which showed the effectiveness of the media in learning. This research confirmed that the utilization of the Assemblr Edu platform in education can enhance engagement and make the learning experience more interactive and enjoyable